Local level Disaster Response in Nepal: Investigating the Government Agencies - Malla, Shrijan Bahadur; Dahal, Ranjan Kumar; Hasegawa, Shuichi (Bulletin of the Department of Geology, 2020)
Effect of local level disaster response is always questionable in Nepal. It is because the capacity of local responding bodies' i.e. local administration, elected representatives and security forces is deficit. Overlooking own role and responsibility by public service offices such as health, water supply, road network, rural development, communication, education has overburdened the responsibility of CDO during disaster response and eroded the effectiveness of cluster approach.  Similarly, over-reliance on security forces from relief and rescue to rehabilitation and reconstruction have also garnered lethargy amongst civil administration and public service offices wearing away their capacity. For that reason, it is utmost important that the prevailing tendency should be altered and derailed local level response mechanism should be brought into the right track.